2020
DOI: 10.1177/1120672120957581
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of pseudomembranous conjunctivitis in a tertiary hospital: A 2-year retrospective study

Abstract: Purpose: To describe the incidence, duration, and complication rate of patients with a clinical diagnosis of pseudomembranous viral conjunctivitis. Methods: A retrospective observational study is performed compiling the data of patients diagnosed as pseudomembranous conjunctivitis at the hospital’s emergency department from June 2016 to May 2018. Demographic variables, duration of symptoms, and follow-up until resolution of the pseudomembranes and associated complications are collected. Results: The incidence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…According to a recent study, pseudomembranous conjunctivitis was associated with subepithelial infiltrates (16.7%), corneal erosion (20.8%) and filamentary keratitis (3.5%). 9 Corneal affection of viral conjunctivitis could have been complicated by MK in our case. Question can arise whether initial conjunctivitis was bacterial (Moraxella) rather than viral.…”
Section: Discussionmentioning
confidence: 57%
“…According to a recent study, pseudomembranous conjunctivitis was associated with subepithelial infiltrates (16.7%), corneal erosion (20.8%) and filamentary keratitis (3.5%). 9 Corneal affection of viral conjunctivitis could have been complicated by MK in our case. Question can arise whether initial conjunctivitis was bacterial (Moraxella) rather than viral.…”
Section: Discussionmentioning
confidence: 57%
“…As a result, pseudomembranous conjunctivitis does not bleed when removed. 4 Here, we report a case of pseudomembranous conjunctivitis from Escherichia coli which, to our knowledge, has not been reported in relevant literature.…”
Section: Introductionmentioning
confidence: 80%
“…Subepithelial infiltrates are believed to represent a cellular immune reaction against viral antigens, deposited in the corneal stroma (22). Histopathologic evaluation of SEIs has shown that they are composed of lymphocytes, histiocytes, and fibroblasts accompanied by a disruption of the collagen Ia, and are thought to be the result of delayed immune response to viral antigens in the corneal stroma (23).…”
Section: Discussionmentioning
confidence: 99%